The Impact of Students' Learning Interests on Learning Outcomes in a Linear Algebra Course - Hanifah, Ayu Ismi; Masruroh, Masruroh (IJECA (International Journal of Education and Curriculum Application), 2022)
Interest is a motivation source that appears in someone on something they like. Learning interest is an interest or more sense to an activity or something from oneself without someone asking. Learning interest existence can impact the quality of learning outcome achievement that is obtained. The type of research used in this research is a survey with correlation analysis. The research problem in this research was to analyze the impact of students' learning interests on learning outcomes. This research aimed to describe the impact of students' learning interests on learning outcomes in a linear algebra course. The data source in this research came from students' learning interest questionnaires and students' final grades on a linear algebra course. The research method used in this research was correlation analysis. Data analysis was conducted by descriptive analysis and a simple linear regression test using SPSS. The results of data analysis obtained indicated that tcount was 3.778 and ttable was 2.008. Therefore, tcount > ttable or it can be concluded that students' learning interests impact learning outcomes in a Linear Algebra course.